(untitled) (Bangladesh Heart Journal, 2016)
Peripartum Cardiomyopathy in association with Diabetes mellitus and Thyroid storm is an extremely rare. Here we describe a young aged Bangladeshi lady, who admitted with progressive breathlessness, high grade intermittent fever, productive cough and altered level of consciousness in Coronary Care Unit. She was a diagnosed case of Diabetes Mellitus and Graves disease but during her last pregnancy the patient voluntarily stopped taking anti-thyroid medication and delivered a healthy male baby through LUCS (two months before admission). After thorough clinical evaluation and laboratory investigations she was diagnosed as having Peripartum Cardiomyopathy, Thyroid Storm, Pneumonia and Metabolic Acidosis. Her condition improved by closely monitored therapy guided by team consisting of Cardiologists, Endocrinologists, Pulmonologists and Gynecologists. There are very few reports in the world which have depicted this unusual association. Bangladesh Heart Journal 2015; 30(2) : 87-91